THE EFFECT OF ENMASROLE THERAPY ON REDUCING THE LEVEL OF ANXIETY OF PREGNANT WOMEN FACING CHILDBIRTH - Prameswari, Veryudha Eka (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Pregnancy is an important period in a mother's life. Changes in pregnant women can trigger psychological problems in pregnant women. The problem that often arises is anxiety, especially in the final trimester when facing the birth process. The body will produce the hormone cortisol, which if excessive can affect the health of the baby and the mother's health.  Anxiety experienced by pregnant women is a condition where a person experiences uncomfortable, unpleasant feelings about thoughts that will happen in the future. In this case, the mother is afraid that the baby will be born at any time under normal conditions, or even die. Anxiety of pregnant women triggers stimulation of uterine contractions. Therefore, the anxiety of pregnant women can be overcome with complementary therapy methods, namely ENMASROLE (Endorphin Massage and Lavender Aroma).  This study aimed to determine the effect of ENMASROLE therapy on reducing maternal anxiety levels in childbirth. Pre-Experiment research method with Pre-Test-Post Test.